HERBAL REMEDIES PREVENTION OF COVID-19 - Anil Kumar Gupta, Manoj Sharma (International Journal of Modern Agriculture, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The disease was first identified in December 2019 in Wuhan, the capital of China’s Hubei province, and has since spread globally, resulting in the ongoing 2019–20 coronavirus pandemic. As of 29 April 2020, more than 3.11 million cases have been reported across 185 countries and territories, resulting in more than 217,000 deaths. More than 932,000 people have recovered. Plant materials are used through developed and developing countries as home remedies, over-the-counter drug products and raw materials for the pharmaceutical industry, and represent a substantial proportion of the global drug market. Some herbal remedies are helpful to improve the immunity system which will be beneficial to prevention of COVID-19.